Pemanfaatan Cendawan Mikoriza Arbuskula dan Bakteri Azospirillum sp. untuk Meningkatkan Efisiensi Pemupukan pada Turfgrass - Dwi Guntoro; M. A. Chozin; Budi Tjahjono; Irdika Mansur (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
Introduction turfgrass varieties require fertilization with high dosage, but it can contaminate environment. The increasing efficiency of fertilizer absorbtion was expected to reduce fertilizer requirement. The experiment was conducted to study the effect of arbuscular mycorrhizae and Azospirillum sp. on nutrient uptake, fertilization efficiency, growth and visual quality of turfgrass. The experiment consisted of two factors, i.e. the dosages of fertilizer and inoculant types. The dosages of fertilizer were the relatif dosage from recommended dosage (RD) i.e 100%RD, 75%RD, 50%RD, and 25%RD. The recommended dosage was 0.5 kg N + 1.5 kg P2O5 + 0.5 kg K2O per 100 m2/month by compound fertilizer (15-15-15). The treatment of 100%RD without inoculant was used as control. The inoculant types were no inoculant, arbuscular mycorrhizal fungi (AMF), Azospirillum sp., and AMF+Azospirillum sp. Factorial experiment was arranged in Randomized Block Design with three replications. The results showed that interaction between inoculant type and dosage of fertilizer affected nutrient uptake, fertilizer efficiency, growth, and visual quality. AMF inoculation and 25%RD increased shoot N uptake and N fertilizer efficiency, compared with control. Azospirillum sp. inoculation at 75% RD increased shoot N concentration, but did not affect on shoot N uptake and N fertilizer efficiency compared with control. Inoculant did not affect shoot P concentration, shoot P uptake, and P fertilizer efficiency. Azospirillum and AMF+Azospirillum inoculation increased shoot K concentration. AMF+Azospirillum inoculation and 100%RD increased shoot N concentration and shoot N uptake, compared with control. Key words : Arbuscular mycorrhizal fungi, Azospirillum, fertilizer efficiency, nutrient uptake, turfgrass.